Thermal Analysis of Chimneys by Finite Element: Thermal analysis (Al-Mansour Journal, 2022)
The study is concerned with effect of thermal stresses on chimneys, where the thermal loads considerate are based on actual field measurements of temperature variation in Al-Dora chimney- Baghdad.These temperature variations are divided into two parts:1- Uniform heating.2- Temperature gradient across the thickness of chimney shell due to flue gases.Thermal analyses were carried out using ACI-307-08 provisions, and STAAD.Pro-V8i using (3D – plate element).Comparison studies in thermal analyses were made on four chimneys similar in dimensions, but different in materials, (Reinforced Concrete, Steel, Stainless Steel, and Aluminum). It was found that the metal chimneys give higher results in radial and vertical displacements, while higher results in the bending moments and membrane stresses were found in the reinforced Concrete chimney.Thermal analyses were carried out to study the effect of chimney shell thickness. It was found that the reactions at the base of the chimney are proportional to the thickness of the shell, but the radial and vertical displacements are inversely proportional with the thickness of the shell, While the effect of changing thickness on the bending moments and membrane stresses was found to be small which indicates that increasing the thickness of shell chimney doesn’t lead to smaller thermal stresses. Finally, it was found that the Uniform heating component is more effective on the bending moments, membrane stresses and vertical displacements, while the rotations were not affected much by thermal loads. Winter time is found to be more critical since it gives higher temperatures gradient.
Keywords: Thermal analysis; Chimney; Finite Element